Characterization of bladder sensory neurons in the context of myelination, receptors for pain modulators, and acute responses to bladder inflammation - Forrest, Shelley L.; Osborne, Peregrine B.; Keast, Janet R. (Frontiers in Neuroscience, 2013)
Bladder sensation is mediated by lumbosacral dorsal root ganglion neurons and is essential for normal voiding and nociception. Numerous electrophysiological, structural and molecular changes occur in these neurons following inflammation. Defining which neurons undergo these changes is critical for understanding the mechanism underlying bladder pain and dysfunction. Our first aim was to define the chemical classes of bladder sensory neurons that express receptors for the endogenous modulators of nociceptor sensitivity, glial cell line-derived neurotrophic factor (GDNF), the related neurotrophic factor, artemin, and estrogens. Bladder sensory neurons of adult female Sprague-Dawley rats were identified with retrograde tracer. Diverse groups of neurons express these receptors, and some neurons express receptors for both neurotrophic factors and estrogens. Lumbar and sacral sensory neurons showed some distinct differences in their expression profile. We also distinguished the chemical profile of myelinated and unmyelinated bladder sensory neurons. Our second aim was to identify bladder sensory neurons likely to be undergoing structural remodelling during inflammation. Following systemic administration of cyclophosphamide (CYP), its renal metabolite acrolein causes transient urothelial loss, exposing local afferent terminals to a toxic environment. CYP induced expression of the injury-related immediate-early gene product, activating transcription factor-3 (ATF-3), in a small population of sacral nitrergic bladder sensory neurons. In conclusion, we have defined the bladder sensory neurons that express receptors for GDNF, artemin and estrogens. Our study has also identified a sub-population of sacral sensory neurons that are likely to be undergoing structural remodelling during acute inflammation of the bladder. Together these results contribute to increased understanding of the neurons that are known to be involved in pain modulation and hyperreflexia during inflammation.